Sub-National Credit Risk and Sovereign Bailouts : Who Pays the Premium? - Jenkner, Eva (IMF Working Papers; Working Paper, 2014)
Studies have shown that markets may underprice sub-national governments' risk on the implicit assumption that these entities would be bailed out by their central government in case of financial difficulties. However, the question of whether sovereigns pay a premium on their own borrowing as a result of (implicitly or explicitly) guaranteeing sub-entities' debt has been explored only little. We use an event study approach with separate equations for two levels of government to test for a simultaneous increase in sovereign risk premia and decrease in sub-national risk premia-or a de facto transfer of risk from the latter to the former-on the day a sovereign bailout is announced. Using daily financial market data for Spain and its autonomous regions from January 2010 to June 2013, we find support for our risk transfer hypothesis. We estimate that the Spanish sovereign's spread may have increased by around 70 basis points as a result of the central government's support for fiscally distressed comunidades autonomas.